PENGARUH PENAMBAHAN MODIFIED STARCH TERHADAP MUTU KAMABOKO SURIMI IKAN MAS - , PIMPIN KUSUMAMURNI, Prihati Sih Nugraheni, S.Pi., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High fat content will inhibit the ability to form a gel and decrease the shelf life. Preliminary researched reduced fat content until 28.35% by soaking the minced fish in 1% of lemon juice, but this treatment also decrease gel strength. Degradation of gel strength surmounted by adding binder agent on kamaboko. Modified starch was one of the binder that never been used in manufacture of processing kamaboko. In this study, kamaboko made by adding 0-7% of modified starch. Characteristic of kamaboko measured by gel strength, whiteness, pH, folding test, proximate content (ash, water, fat, proteins, and carbohydrates content) and sensory test (hedonic and scoring). The result showed by adding 5% of modified starch was the best way to improved the quality of kamaboko. It increased the gel strength up to 1.135 times higher from early gel strength of surimi, gave a pH value 6.41, but decreased the the whiteness until 60.04%. Modified starch influenced the nutrition content of kamaboko by increased the fats and carbohydrate content, but decreased the water, proteins, and ash content in kamaboko. This concentration obtained the highest consumer acceptance, esspecially in texture attibutes. Based on this study it can be concluded that modified starch can be used as an alternative binder in the manufacture of kamaboko.